Takayasu arteritis - N.V. Bortnyak; O.A. Yepanchintseva; A.V. Khokhlov; B.M. Todurov (Кардіохірургія та інтервенційна кардіологія)
Takayasu arteritis is a rare form of the vasculitis of large arteries. It is a disease difficult to diagnose and treat, often unpredictable in terms of outcome and life-treatening. Despite its low prevalence, Takayasu arteritis deserves close attention for therapists, cardiologists, rheumatologists and angiosurgeons. This article presents classifications, features of the clinical course of the disease, possibilities of the visualization diagnosis of the lesions of arteries, assessment of the disease activity. The issues of the contemporary drug therapy, interventional and surgical treatment methods and complications of the disease are presented.